Dianor Resources Inc.: Diamond Market Outlook Enhances Potential of Leadbetter Diamond Deposit Near Wawa, Ontario (Marketwire, 2011)
Demand growth is driven by China and India where urbanisation and an emerging middle class is expected to increase diamond consumption by 21% and 24% respectively over the next year(4). Tight diamond supply in China has seen buyers moving into diamonds not typically satisfied by classical demand; since 2004, the Chinese appetite for diamonds has risen from US$150 million to US$1.2 billion in 2010(5); rough shortages of up to 30% in India is causing Indian diamond cutting and jewellery concerns to seek stable long term supplies overseas(6). Many industry sources estimate that by 2020 the rough diamond shortfall will be in the order of US$5 billion to US$7 billion annually. Current world diamond reserves are estimated at only 15 years at current production levels, (including expansions, new mines and discoveries). Against this scenario, Dianor's Archean conglomerate diamond model is potentially applicable to many areas in the world as recently demonstrated by the discovery of similar diamond-bearing rocks in Cameroon in Africa(7). Dianor is an innovative exploration company focused on advancing diamond exploration properties in the Superior Craton of Canada. The Leadbetter Diamond Project is its most advanced project and is geographically well situated and easily accessible, some 12 kilometres north east of Wawa in Northern Ontario. Substantial exploration work has been conducted on the project since 2005 and in May 2009, the Company received government approval to proceed with a 50,000 tonne bulk sampling programme of the 2.697 Ma old Archean Conglomerate. A preliminary tonnage estimate for this conglomerate is in the range of 549 million to 583 million tonnes (press release July 24th 2007). In addition to diamonds, the conglomerate contains gold, sapphires and rubies (press release January 18th 2007). In 2008, additional diamond discoveries, including rare purple diamonds, were made by the Company in rocks of similar type, age (Archean) and geological settings (press release March 3rd, April 10th,& May 13th 2008) in Quebec. The Quebec diamond properties have increased our portfolio of low cost, accessible exploration targets. These diamond discoveries (Ontario and Quebec) are both unique and amongst the oldest diamond-bearing occurrences in the world. This news release contains statements that may constitute "forward-looking information" or "forward-looking statements" within the meaning of applicable securities legislation. This forward-looking information is subject to numerous risks and uncertainties, certain of which are beyond the control of Dianor Resources Inc. ("Dianor"). Actual results or achievements may differ materially from those expressed in, or implied by, this forward-looking information. No assurance can be given that any events anticipated by the forward-looking information will transpire or occur, or if any of them do so, what benefits that Dianor will derive therefrom. Forward-looking information is based on the estimates and opinions of Dianor's management at the time the information is released and Dianor does not undertake any obligation to update publicly or to revise any of the forward-looking statements, whether as a result of new information, future events or otherwise, except as may be required by applicable securities laws.